Carrying Umbrellas: an Online Relocation Game on a Graph - Lee, Jae-Ha; Park, Chong-Dae; Chwa, Kyung-Yong (Journal of Graph Algorithms and Applications, 2001)
We introduce an online relocation problem on a graph, in which a player that walks around the vertices makes decisions on whether to relocate mobile resources, while not knowing the future requests. We call it Carrying Umbrellas. This paper gives a necessary and sufficient condition under which a competitive algorithm exists. We also describe an online algorithm and analyze its competitive ratio.